Fixed point theorems for α-nonexpansive mappings - Chakkrid Klin-eam (2018)
In this paper, we prove some fixed point theorems of α-nonexpansive mappings introduced by Goebel and Pineda (2007) [1]. Moreover, the demiclosedness principle for theα-nonexpansive mappings is also established. © 2010 Elsevier Ltd. All rights reserved.